Evaluation of the Community Officer Project in Solomon Islands - Dinnen, Sinclair (World Bank, Washington, DC, 2017)
This evaluation assesses the performance of the Community Officer (CO) project, a trial community policing mechanism initiated by the Royal Solomon Islands Police Force (RSIPF) in late 2009, with assistance from the Participating Police Force (PPF) of the Regional Assistance to Solomon Islands (RAMSI). Current interest in community policing in Solomon Islands is occurring in the larger context of the rebuilding and reform of the RSIPF that has been taking place with the assistance of RAMSI. The Solomon Islands Government (SIG) and RSIPF are committed to introducing a viable form of community policing across the country.